Immunomodulatory and Antioxidant Activity of Green Grass Jelly Leaf Extract (Cyclea barbata Miers.) In Vitro - Rasyiid, Mustafid; Mahadi, Rendi; Dharma, Krisnanda Surya; Anggraini, Lindia; Nurdiyanti, Rahma; Nuringtyas, Tri Rini (Advances in Tropical Biodiversity and Environmental Sciences; Vol 2 No 1 (2018): ATBESDO - 10.24843/ATBES.2018.v02.i01.p03, 2018)
Green grass jelly ( Cyclea barbata Miers.) is known for its benefit to human health especially in supporting body’s immune system and wellness. This research aimed to determine immunomodulatory and antioxidant activity of green grass jelly leaf extracts in vitro. Old leaves were collected as sample then dried and ground to powder. The extraction was done with sohxletation using three different solvents, chloroform, ethyl acetate, and ethanol. The immunomodulatory activity was evaluated by treating the crude extracts at concentrations of 50, 100, and 500 mg/mL on macrophages of rat in vitro. The treated macrophage was then challenged for their phagocytic activity to latex beads. The antioxidant activity was done using 1,1-diphenil-2-picrilhydrazil (DPPH) with spectrophotometry technique. All treatments were done with three replicates. Detection of the bioactive groups of the extracts was done by Thin Layer Chromatography (TLC). The results showed that ethyl acetate extract has the highest phagocytic activity followed with chloroform extract and ethanol extract, respectively. Optimum concentration was reached at 100 mg/mL of ethyl acetat extract. The ethyl acetate extract was also the extract with the highest antioxidant activity index 7.7 followed by both extracts of chloroform and ethanol with similar index value of 6.25 and 6.3, respectively. The ethyl acetate extract contained phenolics, flavonoids, tannins, and terpenoids.